2020
DOI: 10.1093/qjmed/hcaa039.060
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Outcome of Methylprednisolone versus Hydrocortisone in Treatment of Acute Respiratory Distress Syndrome(ARDS)

Abstract: Introduction Acute respiratory distress syndrome (ARDS) is the clinical manifestation of severe acute lung injury. It is characterized by dyspnea, profound hypoxemia, diffuse bilateral infiltrates secondary to non-cardiogenic pulmonary edema on chest radiography, and decreased lung compliance and systemic inflammations are the pathophysiologic hallmarks of this syndrome and the use of low-dose corticosteroids was associated with improved mortality and morbidity outcomes without increased adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Unfortunately, it was reported that glucocorticoids resulted in a significant mortality rate in ARDS patients compared to those not receiving high-dose glucocorticoids. However, the efficacy of glucocorticoids has not been investigated in the same categories of patients, as well as the same stages of the illness conditions by the existing studies on ARDS (Elbrassi et al 2020 ). Concurrent use of glucocorticoids in precise illness following ARDS has reduced the number of deaths (Gurganus et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it was reported that glucocorticoids resulted in a significant mortality rate in ARDS patients compared to those not receiving high-dose glucocorticoids. However, the efficacy of glucocorticoids has not been investigated in the same categories of patients, as well as the same stages of the illness conditions by the existing studies on ARDS (Elbrassi et al 2020 ). Concurrent use of glucocorticoids in precise illness following ARDS has reduced the number of deaths (Gurganus et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%